MISCONCEPTION ON STOICHIOMETRIC MATERIAL IN STUDENTS USING THE FOUR-TIER DIAGNOSTIC TEST (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2024)
Chemistry is a difficult science when studying it, which leads to misconceptions. Misconceptions can be identified using The Four-Tier Diagnostic Test. The aim of the research is to find out misconceptions about solar stoichiometry using The Four-Tier Diagnostic Test. The type of research is descriptive and the research approach is qualitative. The research subjects were students of XII IPA 1, 2, 3, and 4 at SMAN 1 Barabai. The object of research is the misconception of stoichiometric materials. The research results showed that from 9 materials, all of them were proven to be misconceptions. The misconceptions are: (1) The formula used is inverted, (2) Wrong calculation of the number of digits, (3) The formula used is wrong, (4) Two different material concepts but are considered the same, (5) Wrong calculation of the number atoms in molecules, (6) Misunderstanding the definition of the concept of matter, (7) Wrongly determining the value of the concept of matter.